JULGAMENTO MORAL EM MENINAS QUILOMBOLA: UM ESTUDO EDUCACIONAL DA COMUNIDADE INVERNADA PAIOL DE TELHA, PARANÁ - Berg, Juliana (2014)
The Quilombola girls from Paiol de Telha community, as part of a traditional group, are in possession of African-Brazilian values that are the basis of their moral judgement. Nowadays however, unequal disputes for land and the Capitalist, white, heteronormative, European supremacy created transformations of their identity and culture, due to careless adaptations in aspects that build their diversity. Today, they express a desire for a school in their community, not only as a means to secure their rights within the law, but also to manifest their freedom in a safe manner. The Paiol de Telha community may be going through a process of gradual dissolution, although it bravely fights to avoid any action towards this course. Here we present, a territorial dispute, beyond the land, for upkeeping of a culture. On one hand, the Swabian Germans, holders of the greater part of the land, that work in favor of their culture and its superposition over any contrary action. On the other hand, the quilombolas from Paiol de Telha, holders of settlements, that fight for decades-past acquired rights of lands that originally belong to them, in the Fundao. Between them, the children of both communities mirror this cultural and social tension, in silencing and prejudiced actions. The study about the judgement in regards to these quilombola girls, whom we consider the most vulnerable ones in this context, brings an useful observation, of how, even in an adverse situation, remains the moral judgement capacity professed by Jean Piaget; in addition, it reaffirms the position of Education as a force able to bring the understanding for the cultural diversity.